Risk Factors of Type 2 Diabetes Mellitus in Elderly - Yulia Afrina Nasution; Zulhaida Lubis; Fazidah Aguslina Siregar (Masters Program in Public Health, 2021)
Backround: Non-communicable diseases arise in the elderly. The degenerative cycle decreases the resistance of the body, so that it is vulnerable to infectious diseases. Diabetes mellitus (DM) is characterized by chronic hyperglycemia and impaired carbohydrates, lipids, and proteins metabolism caused by complete or partial insufficiency of insulin secretion and/or insulin action. This study aimed to examine the risk factors of type 2 DM among elderly at Muhammadiyah General Hospital, North Sumatera.Subjects dan Method: This was a case control study carried out at Muhammadiyah Hospital, North Sumatera, in 2018. A total of 148 elderly patients was selected for this study, consisting of 74 patients with type 2 DM and 74 patients without type 2 DM. The dependent variable was the incidence of type 2 DM. The independent variables were family DM history, smoking habit, physical activity, carbohydrate diet, fiber diet, body mass index (BMI), abdo